Math, asked by Vismehalik5a1pillli, 1 year ago

Factorize : 27p 3 (4q - 2r) 3 + 64q 3 (2r - 3p) 3 + 8r 3 (3p - 4q) 3

Answers

Answered by Golda
63
Solution:-
27p³(4q - 2r)³ + 64q³(2r - 3p)³ + 8r³(3p - 4q)³
= [3p(4q - 2r)]³ + [4q(2r - 3p)]³ + [2r(3p - 4q)]³
Since,
3p(4q - 2r) + 4q(2r - 3p) + 2r(3p - 4q)
= 12pq - 6pr + 8qr - 12pq + 6pr - 8qr = 0
∴ 27p³(4q - 2r)³ + 64q³(2r - 3p)³ + 8r³(3p - 4q)³
= 3×3p(4q - 2r) + 4q(2r - 3p) + 2r(3p - 4q)
= 72pqr(3p - 4q) (4q - 2r) (2r - 3p)
Answer.
Answered by ashishsahoo62
8

Step-by-step explanation:

hope it helps you.............

Attachments:
Similar questions